1994
DOI: 10.1677/joe.0.1430399
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute and repeated intravenous administration of L-692,585, a novel non-peptidyl growth hormone secretagogue, on plasma growth hormone, IGF-1, ACTH, cortisol, prolactin, insulin, and thyroxine levels in beagles

Abstract: L-692,585 is a 2-hydroxypropyl derivative of L-692,429, both novel non-peptidyl growth hormone (GH) secretagogues. The effects of single and repeated intravenous administration of L-692,585 on serum or plasma GH and other hormones in beagles were evaluated. In a balanced 8-dog dose-ranging study, compared to the saline control with a mean (+/- S.E.M.) after-dose serum GH peak of 6.1 +/- 1.3 ng/ml, L-692,585 significantly increased (P < 0.05) peak GH concentrations 4.3-fold (32.5 +/- 7.0 ng/ml) at a dose of 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
40
0
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 6 publications
7
40
0
1
Order By: Relevance
“…T max is about 10 min, which is also in agreement with other GHSs in different species, including man (26)(27)(28)(29).…”
Section: Discussionsupporting
confidence: 88%
“…T max is about 10 min, which is also in agreement with other GHSs in different species, including man (26)(27)(28)(29).…”
Section: Discussionsupporting
confidence: 88%
“…The identification of a specific GHRP receptor in the pituitary, the hypothalamus and other areas of the central nervous system (CNS) (Ong et al 1998, Yokote et al 1998, Chen 2000 has suggested, in the past, the existence of an endogenous ligand for these compounds and this ligand, ghrelin, has been recently identified (Bowers 2001, Kojima et al 2001. The actions of these GHRPs, however, are not specific for GH, as they also stimulate prolactin, adrenocorticotropin (ACTH) and cortisol release in humans and other animals (Jacks et al 1994, Chang et al 1995, Copinschi et al 1996, Arvat et al 1997b. The sites of action for the release of GH by GHRPs are both in the hypothalamus and the pituitary, although the former is seemingly the privileged area (Müller et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…These synthetic GH secretagogues (sGHS), although modelled from Met-enkephalins, have lost the opioid activity and stimulate GH secretion of pituitary somatotroph cells both in vitro and in vivo in a variety of species, including rat, pig and human (Momany et al 1981, Bowers et al 1984, Bowers 1993, Ghigo et al 1994, Arvat et al 1995. Since all these peptides have an oral bioavailability lower than 1%, a number of non-peptidyl sGHS 429,653 and MK 0677), with structures more amenable to chemical modification and optimization of oral bioavailability, have been developed and studied in both animals and man (Cheng et al 1993, Gertz et al 1993, Smith et al 1993, Jacks et al 1994, Chang et al 1995. Among them, the spiroindoline derivative, MK 0677, proved to be the strongest stimulator of GH secretion (Patchett et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of action underlying the GH-releasing activity of peptidyl and non-peptidyl sGHS seem to involve the antagonism of somatostatinergic pathways at both the pituitary and hypothalamic level as well as the stimulation of GHRH-secreting neurones (Conley et al 1995, Hickey et al 1996. Interestingly, the activity of sGHS is not fully specific since a slight stimulatory effect on prolactin, adrenocorticotrophin and cortisol levels as well as influences on the control of sleep and food intake have also been demonstrated ( Jacks et al 1994, Locke et al 1995, Frieboes et al 1995. These actions could take place via activation of specific receptors at levels other than the hypothalamo-pituitary system.…”
Section: Introductionmentioning
confidence: 99%